PERCEPCIÓN DEL PACIENTE FRENTE AL “NIVEL DE ATENCIÓN” DEL SERVICIO DESPLEGADO POR LA PERSONAL ENFERMERÍA QUE LABORA EN EL SERVICIO DE EMERGENCIA DEL HOSPITAL REGIONAL DE ICA (HRICA) EN EL AÑO 2016 - TELLO RAMÍREZ, SAMUEL SALVADOR (2017)
The purpose of this work is to show and demonstrate the level of perception and acceptance of patients, clients or users of the "level of care" provided by the personnel, specifically the specialist staff working in the Emergency Department at HRICA, February-July 2016. The present academic work possesses the characteristic of being a transversal research that includes diverse approaches ranging from experimental, but it also becomes an applied and quantitative research. For the achievement of the significant results we worked with a sample of 50 patients, of which in its totality a participation was witnessed. The technique used for the present investigation was the survey and we had to use the questionnaire as a data collection tool. The product of the present reflects that the population studied yielded positive results with respect to the "level of attention" of the nursing staff in the space detailed above as long as they yielded a result of satisfaction as shown r>0.2; p<0.5. These ratings that we consider positive respond to each of the elements identified and presented to our analyzed population, these variables in turn are closely related to the dimensions of the concept that encompasses the "level of care", these are reliability, responsiveness, safety, empathy and tangible aspects both in the perception of quality and expectation. (r=0.51; p=0.001). We conclude that evidently, as have been ascertained with the hypothesis, there is a relevant link in the existing connection between users' perception and "level of care" of nursing received in the emergency department of patients at HRICA. January- July 2016. KEY WORDS: Perception, service, care, care, acceptance, nursing, emergency.